Socio-economic differences and health seeking behaviour for the diagnosis and treatment of malaria: a case study of four local government areas operating the Bamako initiative programme in south-east Nigeria - Onwujekwe Obinna E; Uzochukwu Benjamin SC (BMC, 2004)
Abstract Background Malaria is one of the leading causes of mortality and morbidity in Nigeria. It is not known how user fees introduced under the Bamako Initiative (BI) system affect healthcare seeking among different socio-economic groups in Nigeria for diagnosis and treatment of malaria. Reliable information is needed to initiate new policy thrusts to protect the poor from the adverse effect of user fees. Methods Structured questionnaires were used to collect information from 1594 female household primary care givers or household head on their socio-economic and demographic status and use of malaria diagnosis and treatment services. Principal components analysis was used to create a socio-economic status index which was decomposed into quartiles and chi-square for trends was used to calculate for any statistical difference. Results The study showed that self diagnosis was the commonest form of diagnosis by the respondents. This was followed by diagnosis through laboratory tests, community health workers, family members and traditional healers. The initial choice of care for malaria was a visit to the patent medicine dealers for most respondents. This was followed by visit to the government hospitals, the BI health centres, traditional medicine healers, private clinics, community health workers and does nothing at home. Furthermore, the private health facilities were the initial choice of treatment for the majority with a decline among those choosing them as a second source of care and an increase in the utilization of public health facilities as a second choice of care. Self diagnosis was practiced more by the poorer households while the least poor used the patent medicine dealers and community health workers less often for diagnosis of malaria. The least poor groups had a higher probability of seeking treatment at the BI health centres (creating equity problem in BI), hospitals, and private clinics and in using laboratory procedures. The least poor also used the patent medicine dealers and community health workers less often for the treatment of malaria. The richer households complained more about poor staff attitude and lack of drugs as their reasons for not attending the BI health centres. The factors that encourage people to use services in BI health centres were availability of good services, proximity of the centres to the homes and polite health workers. Conclusions Factors deterring people from using BI centres should be eliminated. The use of laboratory services for the diagnosis of malaria by the poor should be encouraged through appropriate information, education and communication which at the long run will be more cost effective and cost saving for them while devising means of reducing the equity gap created. This could be done by granting a properly worked out and implemented fee exemptions to the poor or completely abolishing user fees for the diagnosis and treatment of malaria in BI health centres.